Beta blocker dose and markers of sympathetic activation in heart failure patients: interrelationships and prognostic significance. (19th April 2017) - Cohen‐Solal, Alain; Jacobson, Arnold F.; Piña, Ileana L.
Abstract: Aims: Extent of cardiac sympathetic activation can be estimated from physiological parameters, blood biomarkers, and imaging findings. This study examined the prognostic value of three markers of sympathetic activity and their relationship to beta blocker dose in heart failure patients. Methods and results: A post hoc analysis of 858 heart failure subjects in the ADMIRE‐HF trial was performed. Variables related to sympathetic activity were plasma norepinephrine, baseline heart rate, the heart to mediastinum (H/M) ratio of 123 I‐ m IBG uptake, and beta blocker dose. Univariate and multivariate analyses for occurrence of mortality (all‐cause and cardiac) and arrhythmic events were performed. Beta blocker dose was significantly related to age, heart rate, b‐type natriuretic peptide (negatively), body mass index, body weight and plasma norepinephrine. Univariate predictors of all‐cause and cardiac mortality were baseline heart rate ( χ 2  = 4.5, P  = 0.029 and χ 2  = 5 .2, P  = 0.022, respectively), plasma norepinephrine level ( χ 2  = 8.9, P  = 0.0006 and χ 2  = 8.6, P  = 0.003, respectively), and H/M ( χ  = 22.4, P  < 0.0001 and χ 2  = 17.8, P  < 0.0001, respectively). In multivariate analyses, carvedilol‐equivalent dose ( P  = 0.017), plasma norepinephrine ( P  = 0.002), and H/M ( P  = 0.0001) were significant predictors of all‐cause mortality. In separate analyses using multiple measurements of heart rate, mean heart rate >67 b.p.m. was associated with significantly higher cardiac mortality. Conclusions: Higher beta blocker dose was associated with lower mortality, but of the variables associated with sympathetic activity examined, cardiac 123 I‐ m IBG uptake was the most powerful prognostic marker in heart failure patients. Elevated heart rate was associated with greater risk for cardiac death.